On the Variability of Pressure Propagation During Hydraulic Stimulation Based on Seismic Velocity Observations. Issue 2 (1st March 2020) - Schopper, Florian; Doetsch, Joseph; Villiger, Linus; Krietsch, Hannes; Gischig, Valentin S.; Jalali, Mohammadreza; Amann, Florian; Dutler, Nathan; Maurer, Hansruedi
Abstract: Permeability enhancement of a reservoir through hydraulic stimulation is ever so often accompanied by potentially hazardous induced seismicity. Monitoring of in situ pressure propagation remains an important step in understanding the underlying seismo‐hydromechanical processes during hydraulic stimulation and mitigating hazardous induced seismicity. In an effort to monitor pressure propagation remotely, active seismic monitoring was performed during decameter‐scale hydraulic stimulation experiments at the Grimsel Test Site in Switzerland. Using cross‐correlation schemes, subtle traveltime variations that correlate well with the high‐pressure fluid injections during hydraulic stimulation become apparent. The 4‐D seismic tomograms obtained through time‐lapse differential traveltime inversion reveal transient changes in the seismic velocity within the stimulated volume that depend on the effective stress. In‐depth comparison of the seismic velocity variations and measured pressure data indicates that the seismic velocity variations can be used as a proxy for pressure propagation within an equilibrated system. Observations show that traveltime tomography is insensitive to isolated, high‐pressure variations such as a breakthrough within the fracture network. Joint interpretation of the 4‐D seismic tomograms with geological and hydromechanical data reveals fundamental differences between the different experiments due to a large variability in the rock mass response to the hydraulic stimulation. Using the observed velocity variations as a proxy for pressure propagation, we can infer characteristics of the shear zones and the rock volume at the Grimsel Test Site. The observed velocity variations provide not only information on the characteristics of the reservoir itself but also its response to different stimulation techniques. Key Points: Response of seismic velocities to high‐pressure fluid injections provides pressure proxy Four‐dimensional seismic tomograms highlight the differences between injecting fluid into preexisting shear zones and creating new fractures Direct link between pore pressure and observed seismic velocity holds for equilibrated systems but breaks down for isolated pressure fronts